Analysis of Financial Ratio to Assets Financial Performance in Food and Beverage Sub Sector of Manufacturing Companies Listed on the Indonesian Stock Exchange (IDX) for the Period 2019-2022 - Hulaemah, Eem; Ghiffari, Faisal; Uzliawati, Lia (Pertapsi-Indonesia collaborated with Petra Christian University, 2024)
The purpose of this study is to use financial ratio analysis to evaluate the company's financial performance. The food and beverage companies that are listed on the Indonesia Stock Exchange (IDX) for the 2019–2022 timeframe comprise the study's population. Secondary data from the Indonesia Stock Exchange publication is the sort of data that was used. Eight businesses served as the study's samples, which were selected using a purposive sampling technique. Multiple regression analysis is the method of data analysis that is employed. The Eight businesses are PT Tri Banyan Tirta Tbk, PT Wilmar Cahaya Indonesia Tbk, PT Garudafood Putra Putri Jaya Tbk, PT Buyung Poetra Sembada Tbk, PT Indofood CBP Sukses Makmur Tbk, PT Mayora Indah Tbk, PT Sekar Laut Tbk, and PT Ultra Jaya Milk Industry & Trading Company Tbk. The study's findings show that while liquidity has a large positive impact on financial performance, solvency has a large impact on financial performance, profitability has a significant impact on financial performance.